Quorum sensing influences phage infection efficiency via affecting cell population and physiological state. (7th October 2016) - Qin, Xuying; Sun, Qinghui; Yang, Baixue; Pan, Xuewei; He, Yang; Yang, Hongjiang
Abstract : Bacterial growth phase has been reported affecting phage infection. To underpin the related mechanism, infection efficiency of Pseudomonas aeruginosa phage K5 is characterized. When infecting the logarithmic cells, phage K5 produced significantly more infection centers than the stationary cells, well concordant with the viable cell ratio in the different growth phases. Additionally, the burst size decreased dramatically in the stationary cells, implying that the physiological state of the viable cells contributed to the productivity of phage K5, and it was consistent with the expression variation of the phage RNA polymerase. Quorum sensing inhibitor penicillic acid was applied and could significantly improve the viable cell proportion and the infection center numbers, but had less effect on the corresponding burst sizes. Moreover, the effect of penicillic acid and the quorum sensing regulator mutants on the production of phage C11 was also analyzed. Taken together, our data suggest that quorum sensing is involved in the defense of phage K5 infection by influencing the viable cell population and their physiological state, and it is an efficient and intrinsic pathway allowing bacteria to resist phage attacks in natural environment.